Quantitative determination of maitenin and 22β-hydroxymaitenin in callus of Maytenus aquifolium (Celastraceae) by reverse phase high performance liquid chromatography - Corsino, Joaquim [UNESP]; Alécio, Alberto Camilo [UNESP]; Ribeiro, Maria Lücia [UNESP]; Furlan, Maysa [UNESP]; Pereira, Ana Maria S.; Duarte, Ines Batista; França, Suzelei Castro (My University, 1998)
Explants of Maytenus aquifolium were induced to form callus and, subsequently, suspension cultures. The isolation of natural products from callus led to the identification of the cytotoxic triterpene quinonemethides, maitenin (1) and 22β-hydroxymaitenin (2). A rapid, sensitive and reliable reversed-phase high-performance liquid chromatography method was developed using a C18 column and isocratic elution for the determination of 1 and 2. The elaborated method gave well-resolved peaks for these compounds with good detection response and linearity in the range of 0.08-72.0 μg. The quantification of 1 and 2 was performed by an external standard method.
Keywords: 22β-hydroxymaitenin; Callus; Cell culture; Maitenin; Maytenus aquifolium; Quantitative reversed-phase high-performance liquid chromatography